COMMUNICATING HERITAGE THROUGH URBAN SPACE: ANCIENT COMMERCIAL CULTURE AND THE CULTURAL LANDSCAPE OF SHAOXING WATER TOWN - Xia, Ying (Fonseca, Journal of Communication, 2025)
This research examines the relationship between the old business customs of Shaoxing’s water villages and the development of modern cities. The paper tries to compare how Shaoxing water towns grew up with other old commercial centers in China. This shows how different Shaoxing’s commercial habits are and their effect on city growth and culture landscapes. Discoveries show that traditional Shaoxing business keeps the economy going and also helps modern city growth with more culture-related tourism activities. There is a need emphasized by this study for those who make laws to balance the keeping of historical things with the need for new city demands. It proposes policies targeted at blending heritage retention with economic steps forward. With the help of thorough talks with communities and interested parties, the research broadens how we see commercial culture mixing with town developments. The results bring notable insights to those who plan cities, keep cultural history secure, and make policies, showing how keeping cultural history ties with economic running well and giving learnings that might help other towns with deep old business cultures.